Room temperature ppt-level NO2 gas sensor based on SnOx/SnS nanostructures with rich oxygen vacancies. (28th July 2021) - Tang, Hongyu; Gao, Chenshan; Yang, Huiru; Sacco, Leandro; Sokolovskij, Robert; Zheng, Hongze; Ye, Huaiyu; Vollebregt, Sten; Yu, Hongyu; Fan, Xuejun; Zhang, Guoqi
Abstract: In this paper, tin oxidation (SnO x )/tin-sulfide (SnS) heterostructures are synthesized by the post-oxidation of liquid-phase exfoliated SnS nanosheets in air. We comparatively analyzed the NO2 gas response of samples with different oxidation levels to study the gas sensing mechanisms. The results show that the samples oxidized at 325 °C are the most sensitive to NO2 gas molecules, followed by the samples oxidated at 350 °C, 400 °C and 450 °C. The repeatabilities of 350 °C samples are better than that of 325 °C, and there is almost no shift in the baseline. Thus this work systematically analyzed the gas sensing performance of SnO x /SnS-based sensor oxidized at 350 °C. It exhibits a high response of 171% towards 1 ppb NO2, a wide detecting range (from 1 ppb to 1 ppm), and an ultra-low theoretical detection limit of 5 ppt, and excellent repeatability at room temperature. The sensor also shows superior gas selectivity to NO2 in comparison to several other gas molecules, such as NO, H2, SO2, CO, NH3, and H2 O. After x-ray diffraction, x-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscope, and electron paramagnetic resonance characterizations combining first principle analysis, it is found that the outstanding NO2 sensing behavior may be attributed to three factors: the Schottky contact between electrodes and SnO x /SnS; active charge transfer in the surface and the interface layer of SnO x /SnS heterostructures; and numerous oxygen vacancies generated during the post-oxidation process, which provides more adsorption sites and superior bandgap modulation. Such a heterostructure-based room-temperature sensor can be fabricated in miniaturized size with low cost, making it possible for large-scale applications.